2017
DOI: 10.1080/15622975.2017.1282173
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive function in paediatric obsessive-compulsive disorder

Abstract: Youths with OCD exhibited intact performance on memory and EF tests, but slower processing speed, and underperformance only on timed VSA and WM tasks. While the OCD group performed in the normative range, these findings reveal relative weaknesses that may be overlooked. Such an oversight may be of particular importance in clinical and school settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
3
36
1
Order By: Relevance
“…Notably, neither the Park et al study nor the present study found an association between hoarding and the inhibit subdomain. Højgaard et al, 2016) as well as EFs (i.e., EF task underperformance does not seem to be a characteristic of pediatric OCD; Abramovitch et al, 2015a;Geller et al, 2017;Hybel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, neither the Park et al study nor the present study found an association between hoarding and the inhibit subdomain. Højgaard et al, 2016) as well as EFs (i.e., EF task underperformance does not seem to be a characteristic of pediatric OCD; Abramovitch et al, 2015a;Geller et al, 2017;Hybel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Performance-based EF underperformance in OCD has been supported in metaanalyses based on adult samples with small to medium effect sizes (ES; Abramovitch, Abramowitz, & Mittelman, 2013;Shin, Lee, Kim, & Kwon, 2014;Snyder, Kaiser, Warren, & Heller, 2014), but, performance-based EF underperformance in children and adolescents is generally not supported (Abramovitch et al, 2015a;Geller et al, 2017;Hybel, Mortensen, Lambek, Thastum, & Thomsen, 2016). Contrary to studies of performance-based EFs, the literature on rating-based EFs in OCD is rather limited and solely based on child and adolescent samples.…”
Section: Executive Functions In Ocdmentioning
confidence: 99%
“…The few neuropsychological studies in youths with OCD have yielded inconsistent results (Abramovitch et al 2015 ). Visuospatial memory has been found to be impaired among juvenile patients in some (Andrés et al 2007 ; Chang et al 2007 ; Lewin et al 2014 ) but not in other studies (Shin et al 2008 ; Zandt et al 2009 ; Ornstein et al 2010 ; Geller et al 2017 ; Hybel et al 2017 ). For cognitive flexibility and set shifting, some studies have shown impairments in youths with OCD (Andrés et al 2007 ; Shin et al 2008 ; Isik Taner et al 2011 ; Gruner et al 2012 ), while others found no deficits (Beers et al 1999 ; Ornstein et al 2010 ; Kodaira et al 2012 ; Hybel et al 2017 ).…”
Section: Introductionmentioning
confidence: 94%
“…Another limitation of previous studies is the inclusion of patients with comorbidities. While it has been reported that around half of youth with OCD fulfil criteria for anxiety or depressive disorder, with another 16% suffering from externalizing disorders (Peris et al 2017 ), previous studies have tested patients with a wide range of comorbidities, including depression, generalized anxiety disorder, post-traumatic stress disorder, specific or social phobia, separation anxiety disorders, ADHD, oppositional defiant disorder and Tourette's syndrome (Chang et al 2007 ; Britton et al 2010 ; Huyser et al 2010 ; Ornstein et al 2010 ; Gruner et al 2012 ; Kodaira et al 2012 ; Lewin et al 2014 ; Geller et al 2017 ). Though some of these disorders might share overlapping impairments, the different profiles of comorbidities add to the heterogeneity of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…Next are the illness-specific factors associated with OCD in youth that are not seen as frequently in adults and that may require specialist knowledge and intervention. These include symptom-specific presentations or symptom dimensions in young patients (Geller et al, 2001b, Stewart et al, 2007, a unique and developmentally-specific profile of common comorbid psychiatric disorders (Geller et al, 2001b), a unique pattern of neurocognitive deficits (Geller et al, 2017), increased familial aggregation of early-onset OCD (Rosario-Campos et al, 2001, Walitza et al, 2010, Taylor, 2011, high rates of family accommodation as a consequence of children being embedded in family units and perhaps environmental or epigenetic influences that occur at a sensitive period of neural maturation . Recently it was shown that serotonin transporter-gene methylation levels were significantly higher in children and adolescents with OCD compared to controls and adult patients with OCD.…”
Section: Early Intervention For Children and Adolescents With Ocdmentioning
confidence: 99%